2015
DOI: 10.1073/pnas.1421174112
|View full text |Cite
|
Sign up to set email alerts
|

Avoided valence transition in a plutonium superconductor

Abstract: The d and f electrons in correlated metals are often neither fully localized around their host nuclei nor fully itinerant. This localized/ itinerant duality underlies the correlated electronic states of the high-T c cuprate superconductors and the heavy-fermion intermetallics and is nowhere more apparent than in the 5f valence electrons of plutonium. Here, we report the full set of symmetryresolved elastic moduli of PuCoGa 5 -the highest T c superconductor of the heavy fermions (T c = 18.5 K)-and find that the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
43
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 45 publications
3
43
0
Order By: Relevance
“…This proves that for CeCoIn 5 at p L the spin fluctuations responsible for the intrinsic Kondo liquid T 1 exhibit quantum critical magnetic behavior, and suggests a possibly similar situation in PuCoGa 5 . We note that recent elastic moduli measurements have observed an anomalous softening of the bulk modulus in PuCoGa 5 and suggested that valence fluctuations may play a critical role in its superconductivity [20]. Combining their results and the NMR measurement [1] suggests that both valence and spin fluctuations may be involved to give rise to the particularly high T c in this interesting compound.…”
supporting
confidence: 61%
“…This proves that for CeCoIn 5 at p L the spin fluctuations responsible for the intrinsic Kondo liquid T 1 exhibit quantum critical magnetic behavior, and suggests a possibly similar situation in PuCoGa 5 . We note that recent elastic moduli measurements have observed an anomalous softening of the bulk modulus in PuCoGa 5 and suggested that valence fluctuations may play a critical role in its superconductivity [20]. Combining their results and the NMR measurement [1] suggests that both valence and spin fluctuations may be involved to give rise to the particularly high T c in this interesting compound.…”
supporting
confidence: 61%
“…The occurrence of valence fluctuations in PuCoGa 5 has been recently suggested by resonant ultrasound spectroscopy measurements, showing that the three compressional elastic moduli exhibit anomalous softening upon cooling, which is truncated at the SC transition [14]. These results have been interpreted as evidence for a valence transition at a T V < T c that is avoided by the superconducting state [14].…”
mentioning
confidence: 75%
“…These results have been interpreted as evidence for a valence transition at a T V < T c that is avoided by the superconducting state [14]. On the other hand, the relaxation…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…A consequence of this realization is that no single-configuration electronic-structure model has succeeded or even can succeed in accounting for either large changes in the bulk modulus with temperature or the negative thermal expansion. In the superconductor PuCoGa 5 , measurements have shown that multiple plutonium valence configurations lead to unusual elastic softening (7). Earlier inelastic neutron-scattering measurements by Trouw et al (8), confirmed by the statistically improved recent neutron-scattering measurements by Janoschek et al (6), reveal that multiple electronic configurations are present in δ-Pu that are also thermally accessible with the higher energy state approximately 1,400 K above the ground state.…”
mentioning
confidence: 96%